ANALISIS MEKANISME TERJADINYA TEKANAN-LUAP DAN PREDIKSI TEKANAN PORI PADA LAPANGAN BD, CEKUNGAN JAWA TIMUR - Ryan Surjaudaja; Agus Mochamad Ramdhan; Indra Gunawan (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2017)
The East Java Basin is one of the sedimentary basins with proven petroleum system and very prospective as an exploration target. However, drilling in this basin is a risky operation because of the presence of overpressure, which is shown by kick and lost during exploration wells drilling in BD Field as an example. Drilling problems and drilling risks can be reduced by doing overpressure study, including overpressure generating mechanism, pore pressure prediction, and estimation top of overpressure. The temperature in this field can reach 80°C at the depth around 1500 m SSTVD. However, the Dutta-Katahara crossplot does not indicate any diagenesis of smectite to illite. It is also confimed by XRD data in one of the well, which shown domination of kaolinitic clay mineral. Based on the vitrinite reflectance data, there is no transformation of kerogene to hydrocarbon in this field. The burial history plot shows rapid sedimentation with the rate of 1723 m/million years. Based on those criterias, the main overpressure generating mechanism is interpreted to be loading mechanism. High sedimentation rate is related to the peak inversion in Plio-Pleistocene time, providing abundant of sediment supply into the basin. Pore pressure in this field can be estimated by using sonic data with Eaton’s method. Both direct and indirect pressure measurements, combine with drilling data are used to support this estimation. Based on well data, top of overpressure in this field is located at the depth around 1500-1600 m SSTVD. The top of overpressure is located within Lidah Formation.